2016
DOI: 10.14693/jdi.v23i1.982
|View full text |Cite
|
Sign up to set email alerts
|

Dental and Periodontal Status of 5 and 12 year old Children in Jakarta and it’s Satellite Cities

Abstract: Jakarta is the capital city of Indonesia which is surrounded by its satellite cities Bogor, Depok, Tangerang, Bekasi. Nonetheless, scarce information are available of the current oral health of children. Objective: The study aims to describe caries and gingival status among 5 and 12 years old children in Jabodetabek. Jabodetabek is an abbreviation of Jakarta, the capital city of Indonesia, and the satellite cities in its surrounding (Bogor, Depok, Tangerang, Bekasi). Methods: The survey was done in 2014 and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
1
23
1
Order By: Relevance
“…Contradictorily, Korea and Hong Kong had very high HDI scores, but their caries prevalence was high (>50%) compared with their counterparts in Europe. Furthermore, 11 studies in Asia reported mean dmft scores equivalent to or higher than 3 . It is noteworthy that the HDI can indicate only the development level of the entire country, and that the socioeconomic status of an individual city or district cannot be reflected in this index, which is a limitation of the present review.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Contradictorily, Korea and Hong Kong had very high HDI scores, but their caries prevalence was high (>50%) compared with their counterparts in Europe. Furthermore, 11 studies in Asia reported mean dmft scores equivalent to or higher than 3 . It is noteworthy that the HDI can indicate only the development level of the entire country, and that the socioeconomic status of an individual city or district cannot be reflected in this index, which is a limitation of the present review.…”
Section: Discussionmentioning
confidence: 80%
“…An initial screening of the title and abstract revealed that 551 articles were duplicates and 1707 articles did not meet the inclusion criteria. Full texts of the remaining 152 articles were assessed, and 37 studies were included in the present study . No additional publications were identified from the bibliography of these 152 articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The centers of disease control and prevention of United States reported the prevalence of early childhood caries (ECC) reached 28% of all toddlers and preschoolers in the U.S. and that almost half of the number of U.S. children had the ECC before entering kindergarten [2]. A comprehensive review of studies in Europe, Africa, Middle East, and North America also revealed the prevalence of childhood dental caries reached 70% and the highest prevalence was found in Africa and Southeast Asia [3][4][5].…”
Section: Introductionmentioning
confidence: 99%